2021
DOI: 10.26751/jikk.v12i1.886
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Nilai Keislaman Melalui Caring Pemenuhan Kebutuhan Spiritual Sholat Pasien Rawat Inap

Abstract: One of the spiritual needs of Muslims is prayer. Prayer must be done in a state of illness with different procedures according to ability. The purpose of this study was to determine the relationship between the ability of patients and the role of nurses in the application of Islamic Caring for Spiritual Needs. Cross Sectional Sample 50 people. Chi-Square data analysis. The results of the ability of patients with the fulfillment of the spiritual needs of prayer (p value 0.006 <0.05), the role of nurses in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…A research that high intellectual experience can provide a broader spiritual outlook that affects the health of his soul (9). In contrast to other research that there is no relationship between education level and Patient Satisfaction Spiritual Care (10). According to that one outcome of higher education is satisfaction or dissatisfaction with the product or service (1).…”
Section: B Education Of Respondentsmentioning
confidence: 95%
See 2 more Smart Citations
“…A research that high intellectual experience can provide a broader spiritual outlook that affects the health of his soul (9). In contrast to other research that there is no relationship between education level and Patient Satisfaction Spiritual Care (10). According to that one outcome of higher education is satisfaction or dissatisfaction with the product or service (1).…”
Section: B Education Of Respondentsmentioning
confidence: 95%
“…A research which explains that hospitalized patients experience a condition of spiritual distress (11). The explain spiritual distress is a condition in which a person experiences a lack of connection with living with his or her beliefs (10). When a person is sick, feels pain or loss attacks someone, spiritual power can help a person to heal (12).…”
Section: Description Patient Satisfaction Spiritual Care On Pre Test ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sedangkan sebanyak 37.5% pasien dengan kemampuan berjalan masuk dalam kategori belum terpenuhi kebutuhan akan solat. Hal ini menunjukkan bahwa makin lemah pasien yang dirawat di rawat inap maka kebutuhan akan solat makin kecil [18].…”
Section: Pembahasanunclassified
“…Engaging in murottal, or listening to the holy verses of the Quran, has a calming effect on the listener. Research by (14) has demonstrated that listening to these verses can effectively address various types of mental disorders. Consequently, this study seeks to explore the impact of murottal therapy on anxiety and depression in individuals diagnosed with coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%